Assessment of undergraduates’ preferences and opinions on teaching of Pharmacology - Bukar, B. B.; Falang, K. D.; Gyang, S. S. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The preference and opinion of undergraduate students on teaching of pharmacology was assessed using structured-based questionnaires. The objective was to determine the best way to teach pharmacology and the areas the students prefer most. Methods: The questionnaires were administered to students during academic sessions in any of their pharmacology lectures by the help of technical assistants. It was also ensured that the identity of the students was not made known except for the gender. A total of 8 questions with options ranging from 2-4 were used. Each respondent was to select only one option as the most preferred. A total of 405 students participated during the study period and it was ensured that no student participated more than once. The students recruited were 4th and 5th year medical and pharmacy students of the University of Jos, Jos, Nigeria for the 2014/2015 and 2015/2016 academic sessions. Results: The results showed that the students have high preference for latest technology teaching aids such as power point presentation and use of software for lecture notes. Conclusions: Knowledge of pharmacodynamics, clinical pharmacology and laboratory experiment were preferred and significant differences exist between observed and expected results and also between males and females in preferences among some of the options. Students need to be informed at the beginning of their lectures that pharmacology is a subject that must be regarded as a whole with no areas of preference.